2008
DOI: 10.1039/b810631b
|View full text |Cite
|
Sign up to set email alerts
|

Soft material with intense photoluminescence obtained by dissolving Eu2O3 and organic ligand into a task-specific ionic liquid

Abstract: A task-specific ionic liquid containing a carboxylate group with the ability to dissolve metal oxide and organic ligands has been used as the solvent to prepare lanthanide complexes without the addition of extra solvent; thus a soft material with intense photoluminescence has been obtained by directly dissolving Eu(2)O(3), 2-thenoyltrifluoroacetone (TTA) and 1,10-phenanthroline (Phen) into the task-specific ionic liquid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…The lifetime, radiative (A rad ), and nonradiative (A nrad ) transition rates are related through Equation (1). [21] 1…”
Section: Resultsmentioning
confidence: 99%
“…The lifetime, radiative (A rad ), and nonradiative (A nrad ) transition rates are related through Equation (1). [21] 1…”
Section: Resultsmentioning
confidence: 99%
“…The solubility of CO2 in the used ILs was at least 10 -20 times higher than its solubility in the conventional solvents, polymer matrices or water, 27 that could be a result of the formation of weak acid-base complexes between CO2 (the electron-pair acceptor) and the IL anion (the electron-pair donor). 109,[116][117][118] Additionally, the hydrophobic polydimethylsiloxane-based silicone matrix exhibited excellent permeability to CO2. 81 The sensitivity of the CO2 sensors depended on the indicator pKa, the nature of the counterion of IL, and the nature of the base used in the internal buffer solution.…”
Section: ·6 Other Functionsmentioning
confidence: 99%
“…Li et al 116 used a task-specific IL 3-(5-carboxypropyl)-1-methylimidazolium bromide as the solvent for Eu2O3 and the organic ligands (2-trenoyltrifluoroacetone and 1,10-phenantroline) to prepare a soft, transparent, and highly luminescent material. The IL dissolved the Eu(III) oxide because the carboxylic acid from the IL reacted with Eu2O3 to form carboxylate complexes.…”
Section: ·6 Other Functionsmentioning
confidence: 99%
“…The excitation and emission spectra were performed on a Hitachi F-4500 spectrophotometer equipped with a 150 W xenon lamp as the excitation source. and Eu 3+ ions and the * transitions of the organic ligands [10] . Several discrete f-f transitions can be observed at 467 ( nides due to the tunable properties of ILs.…”
Section: Characterizationmentioning
confidence: 99%
“…Puntus et al have reported that when 1-dodecyl-3-methylimidazole chloride ([C 12 mim][Cl]) was doped with 1 mol.% of the lanthanide ternarycomplexes [Ln(TTA) 3 (phen)] (TTA=thenoyltri-fluoroacetonate, phen=1, 10-phenanthroline, Ln= Nd, Eu, Er, Yb), the photoluminescence properties were enhanced [9] . Li et al have reported a facile method to prepare highly luminescent soft materials by directly dissolving lanthanide oxides and organic ligands (2-Thenoyltri-fluoroacetone (TTA) and 1, 10-phenanthroline (Phen)) in carboxyl-functionalized IL [10,11] . ILs are good solvents for the emission properties of lanthanide ions.…”
mentioning
confidence: 99%